A Manuscript Anthology of the Resolutions of Church Congresses (Sobory) and Other Essays of the Filippovtsy in the Collection of the Wróblewski Library, Lithuanian Academy of Sciences - Morozova, Nadežda (Slavistica Vilnensis, 2019)
The article analyzes the handwritten anthology of resolutions of church congresses (sobory), polemical letters, and other essays of the Filippovtsy, donated to the Wroblewski Library of the Lithuanian Academy of Sciences (WLLAS, F19-331) in the autumn of 2018. The book contains 188 sheets; it is a manuscript convolute composed of several scattered “brochures,” written on different paper with different handwritings — the poluustav (semi-uncial) and the civil cursive of the 19th century. The study showed that the manuscript was created (more precisely, merged in one book (bound) from separate and multi-temporal documents) in the mid-1880s, most likely in Moscow, in the Filippovtsy concord center at Bratsky Dvor. The collection includes 34 texts (resolutions of 14 Filippovtsy church congresses as well as the most important polemical and dogmatic essays and letters of authoritative mentors and other figures of this Old Believer community). The earliest texts are dated to the 1810s, the most recent ones are from the mid-1880s, but not earlier than 1883.
Keywords: Old Believers; Filippovtsy; manuscripts; literary traditions; Filippovtsy concord Moscow center Bratsky Dvor; Wroblewski Library of the Lithuanian Academy of Sciences